PENGARUH PELARUT N-HEKSANE DAN ETANOL PADA MIKROKRISTALIN SELULOSA DARI DAUN JAMBU BIJI (Psidium Guajava L) SEBAGAI EKSIPIEN OBAT - Vinsensius Fererius Cakreswara Acintyas; Amanda A. A. Dos Santos; Yunica Nur Witanjaya; Dewi Wahyuningtyas (PROSIDING SNAST, 2018)
Microcrystallin cellulose (MCC) is a pure ceullose that isolated from several alpha cellulose natural sources such as woody plants, cotton husk, or baggase. It can be applied as drug excipients in medical sector. Cellulose raw materials obtained from guava leaves as effective as a natural diarrhea medicine. This research aimed to study the addition of guava leaf to synthesis microcrystallin cellulose and to compare the characteristics microcrystallin cellulose from guava leaf with Avicel PH 102 as a standard commercial microcrystallin cellulose. The research methods consisted of several processes: 1) Extraction of guava leaves with n-Heksane dan Etanol volume comparisons variation: 3:0; 2:1; 1:2; 3:0 in 350 grams of guava leaf weight, 2) Delignification process stages using base (NaOH) solution, 3) Bleaching process with NaOCl solution , and 4) Hydrolysi processs of alpha cellulose by using dilute acid (HCl) solution at high temperature. The characteristics of microcrystallin cellulose were analyzed by organoleptic test, pH, solubility and loss on drying. The results showed that the ratio of solvent n-hexane and ethanol 2:1 volume was the optimal point obtained after observed from several tests performed has the maximum percentage of alpha cellulose is 4.11% and the percentage of microcrystallin cellulose is 3.71%. The organoleptic characteristic such as powder, white, odorless and tasteless were fine. Solubillity in water was 0.16% and pH was 5.15. The loss on drying was 5.88%. Microcrystallin cellulose from guava leaf generally met the pharmacopeia requirements and the characteristics were not significanlly different from Avicel PH 102.